ASAS KEMATANGAN SOSIAL DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN - Rino Ardian Septendra; M. Amir Mahmud; Akhmad Rudi Maswanto (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Marriage is a very important aspect of human life around the world, so it is not surprising that religions around the world regulate marriage; even traditions, customs of society, and state institutions are not left behind in regulating marriage. This research uses a conceptual approach. The data source used entirely uses literature research, while secondary data is used as a way to examine the primary data studied. Data collection techniques use descriptive analysis. The data analysis uses content analysis as an effort to provide comparisons to find suggestions and solutions, and conclusions are drawn. The results showed that the factor that forms the norm of the principle of social maturity is gender, especially because it is the basis for distinguishing between an assessment of biological and psychological maturity and, furthermore, religious traditions that can be the beginning of an understanding of the minimum age of marriage. In terms of the use of the principle regarding age limitsÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Âat least a principle that is commensurate with the principle that has been previously used, namely the principle of being old enough-this principle as a legal category is actually sufficient to represent the expectations or ethical demands of legal material. However, it is less able to provide certainty by providing open access for the community to participate.